Desire Never Leaves : The Poetry of Tim Lilburn - Lilburn, Tim, 1950- (Book collections on Project MUSE., 2007)
The selected poems in "Desire Never Leaves" span Tim Lilburn's career, demonstrating the evolution of a unique and careful thinker as he takes his place among the nation's premier writers. This edition of his poetry untangles many of the strands running through his works, providing insight into a poetic world that is both spectacular and humbling. The introduction by Alison Calder situates Lilburn's writing in an alternate tradition of prairie poetry that relies less on the vernacular and more on philosophy and meditation. Examining Lilburn's antecedents in Christian mysticism and the ascetic tradition, Calder stresses the paradoxical nature of Lilburn's writing -- the expression of loss through plenitude. The divine in the natural world is glimpsed in brief flashes; nevertheless, the poet, driven by love, continues his quest for what glitters in things. Tim Lilburn's afterword is an evocative meditation grounded in personal history. He speaks of how poetry, a craning quiet, allows one to hear what is alive in the world. He also describes how poetry is resolutely attached to both a historical moment and an individual subjectivity that is inevitably anchored in time. Lilburn's poetry is both a religious undertaking and a political gesture that speaks to the urgency of situating ourselves where we live.